INTERPRETING THE READABILITY IN SIMPLIFIED EDITIONS OF CHILDRENâ€™S LITERATURE FROM A THEMATIC PERSPECTIVE: A CASE STUDY ON ALICEâ€™S ADVENTURES IN WONDERLAND - Wang, Tingjia (Indonesian Journal of Applied Linguistics, 2017)
Readability formulas developed on the foundation of the structuralist approach have been proven capable of providing satisfactory indexes about the readability in most cases, but cannot explain â€œcauses of difficulty or... how to write readablyâ€ (Klare, 1974, p. 62). This paper will explore the thematic structure under the framework of Systemic Functional Linguistics as an explanation perspective for the achievement of readability in simplified editions of childrenâ€™s literature. The study is based on a comparison between the original and two simplified editions of Aliceâ€™s Adventures in Wonderland in terms of Theme composition and Theme status, respectively. The two adaptations have provided explicit conjunctions and an explicit identity chain, respectively, as the major tool to assist young readers with reading. Green (1865) has foregrounded the tactic relationship between clauses by adding Textual Theme back to the clause and by revising the clausal order in complexes. Swan (1988) has omitted most Textual Themes either on purpose or along with the deletion of plots, and rewritten marked Themes into unmarked, modifying the development of text into a linear pattern and converging the clausal order in text towards that in spoken language.